The ‘Nigerian Diet’ and its evolution: review of the existing literature and household survey data - Petrikova, I.; Bhattacharjee, Ranjana; Fraser, P.D. (MDPI, 2023)
Natural and social science studies have commonly referenced a ‘typical’ or ‘habitual’ Nigerian diet, without defining what such a diet entails. Our study, based on a systematic review of the existing literature and an analysis of household-level survey data, describes the general outline of a common Nigerian diet and how it varies based on spatial, demographic, and socio-economic characteristics. We further try to establish whether Nigeria has embarked on a dietary transition common in most modern economies, marked by a greater consumption of processed foods, fats, and sugar at the expense of traditional whole cereals and pulses. We conclude that while a traditional Nigerian diet is still relatively healthy from an international perspective, it has indeed been transitioning, with an increasing inclusion of high-energy, high-fat, and high-sugar processed foods and a related growing incidence of overweight, obesity, and diet-related non-communicable diseases.